The active method in the development of reading and writing in middle school students - Quiroz Cedeño, Jessenia Auxiliadora (International research journal of management, IT and social sciences, 2025)
Literacy is a basic process in developing cognitive skills that begins in the first years of education; sometimes it presents as a deficit in the first years of learning since it is where they acquire basic skills such as reading and writing. The objective was to analyze the active methods in the development of reading and writing in secondary basic education students. The methodology used was quantitative and qualitative, experts carried out the validation of the instruments, an observation sheet and a survey were applied to a sample of 35 fifth-year students and 6 teachers from the same sublevel of the Dr. Gonzalo Abad Grijalva Educational Unit of the Chone-Manabí canton, Ecuador, school year 2023-2024. The result was that 89% of the observed students did not read at an adequate speed for the educational level and 83% did not read with fluency and intonation; 27% do not review or correct errors when writing and 23% do not have originality when writing. In contrast, 21% show interest in reading and writing and 33% prefer to work with the active approach.